Adaptation Principles : A Guide for Designing Strategies for Climate Change Adaptation and Resilience - Hallegatte, Stephane (World Bank, Washington, DC, 2020)
Effective action on resilience and climate change adaptation can be a complex task—requiring coordinated efforts from the highest levels of government to individual households and firms. The Adaptation Principles offer a guide to effective climate change adaptation, containing hands-on guidance to the design, implementation and monitoring of national adaptation strategies. It specifies six guiding principles, which correspond to common policy domains: 1) Ensuring resilient foundations through rapid and inclusive development; 2) Facilitating the adaptation of firms and people; 3) Adapting land use and protecting critical public assets and services; 4) Increasing people’s capacity to cope with and recover from shocks; 5) Anticipating and managing macroeconomic and fiscal risks; 6) Ensuring effective implementation through prioritization and continuous monitoring. While outlining these universal Adaptation Principles, this guide shows that each country needs to tailor these actions to its specific needs and priorities. To guide this process, Adaptation Principles offers concrete and practical tools: Screening questions to identify the most urgent and effective actions, toolboxes illustrating common datasets and methodologies to support decisions, indicators to monitor and evaluate progress, and case studies on how the COVID-19 pandemic influences priorities in taking effective adaptation action.